Integration Of Religion Into Curriculum Design And Educational Institution Identity - Ahmed Al-Farisy; Meriem Nasser Suhaeni; Devid Tabilo Satelo; Eleimera Chiriace; Laila Martinez Robaz (International Journal of Education Management and Religion, 2024)
This study aims to explore the influence of religion on curriculum design and the identity of educational institutions. In the context of religious-based education, curriculum design does not only focus on the development of academic knowledge but also on shaping the character of students in accordance with the values of the religion followed. This research uses a qualitative approach with a library research method, examining literature related to the application of religious teachings in curricula and educational cultures at various religious-based educational institutions. The results show that the integration of religion in the curriculum produces a holistic educational approach that connects spiritual and intellectual aspects in the learning process. Furthermore, the identity of educational institutions is greatly influenced by the religious values applied in the curriculum, distinguishing these institutions from general education institutions. The influence of religion is not limited to the teaching of religious subjects but also affects the approach in other subjects, creating an educational environment that reflects religious values. This study also found challenges in integrating religion into curricula in pluralistic environments, which requires an inclusive approach that respects diversity. Therefore, it is essential for religious-based educational institutions to design a balanced curriculum that considers religious values while remaining open to cultural and religious diversity in the classroom.